Pengaruh Earning Per Share, Economic Value Added, Market Value Added, Return On Equity, dan Debt to Equity Ratio Terhadap Return Saham - Tjahjani Murdijaningsih; Diah Retnowati; Ali Jufri; Imam Hadiwibowo (Majalah Imiah Manajemen & Bisnis, 2022)
This study aims to determine the effect of earnings per share, economic value added, market value added, return on equity, and debt to equity ratio on stock returns of companies that are members of the IDX 30 on the Indonesia Stock Exchange. This study uses panel data regression analysis. The results of this study indicate that earnings per share and economic value added do not have a significant effect on stock returns, market value added and debt to equity ratio have a significant negative effect on stock returns, return on equity has a significant positive effect on stock returns. The implication in this study is that companies need to increase their net profit activities by streamlining costs or increasing their business activities and need to make effective management of existing capital by placing capital only for productive activities and reducing unnecessary costs. In addition, managers need to maximize the difference between the market value of the company's equity and invested equity capital by properly managing outstanding shares